The Economic Impact of the Sharing Economy on Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Bagas Kurniawan; Egi Susanto; Eni Rahmawati; Abdul Nasir (Economica Insight, 2026)
The sharing economy is a digital platform based economic model that enables individuals and business actors to participate in the production, distribution, and consumption of goods and services through collaborative systems. This study aims to evaluate the economic impact of the sharing economy on Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in 2025 by reviewing secondary data, government reports, and recent academic studies. The findings indicate that the sharing economy expands market access, increases business turnover, and accelerates the digitalization of MSMEs. However, challenges such as limited digital literacy, inadequate technological infrastructure, and increasing platform competition remain significant obstacles that must be addressed. This study provides recommendations to strengthen MSMEs within a sustainable digital ecosystem.